Boron Toxicity Causes Multiple Effects on Malus domestica Pollen Tube Growth - Fang, Kefeng; Zhang, Weiwei; Xing, Yu; Zhang, Qing; Yang, Liu; Cao, Qingqin; Qin, Ling (Frontiers in Plant Science, 2016)
Boron is an essential micronutrient for plants. However, boron is also toxic to cells at high concentrations, although the mechanism of this stress is not known. This study aimed to evaluate the effect of boron stress on Malus domestica pollen tube growth and its possible regulatory pathway. Our results show that a high concentration of boron inhibited pollen germination and tube growth and led to the morphological abnormality of pollen tubes. Fluorescent labeling coupled with a scanning ion-selective electrode technique detected that boron stress could decrease [Ca2+]c and induce the disappearance of the [Ca2+]c gradient, which are critical for pollen tube polar growth. Actin filaments were therefore altered by boron stress. Immuno-localization and fluorescence labeling, together with Fourier-transform infrared analysis (FTIR), suggested that boron stress influenced the accumulation and distribution of callose, de-esterified pectins, esterified pectins and arabinogalactan proteins in pollen tubes. All of the above results provide new insights into the regulatory role of boron in pollen tube development. In summary, boron likely plays a structural and regulatory role in relation to [Ca2+]c, actin cytoskeleton and cell wall components and thus regulates Malus domestica pollen germination and tube polar growth.